Penggunaan Metode Proyek Untuk Mengembangkan Kemampuan Kerjasama Pada Anak Kelomok A di TK Widyapura Laweyan Surakarta - Ratri Nuria (STAI Terpadu Yogyakarta, 2018)
This study aimed to develop a social competent specially cooperative learning at children for 4-5 age in TK WIDYAPURA. This study includes action research. Subject that was researched A groub of kindergarten. Data has been collected for this research is child’s data and teacher’s data. Child’s data is observation about cooperative competent by project method, while teacher’s data is observation of learning by project methode. The Result of reseach for every cycle is increasingly before of action research is 40%, and after action research for cycle I is 67,2%, cycle II is 88,9% and cycle III is 92,7%. Based on Result of this research is projectmethode can develop cooperative competent at children.